Analisis Beban Kerja dan Jumlah Pekerja Menggunakan Metode Workload Analysis (Studi Kasus: PT. Metal Stamping) - Muhammad Reza Aldiansyah; Kusnadi Kusnadi (Universitas Negeri Gorontalo, 2023)
PT. Metal Stamping is a company engaged in Metal Processing that produces motorcycle parts, filters & radiator parts which in the production process of course use the power of the workers. This can cause an overload of workload experienced by production operators in the Production Department 2. In an effort to solve this problem in this study using the Workload Analysis method, namely with the aim of being able to find out the amount of physical workload experienced by the operator and analyze the optimal number of production operators in the AIDA 250, AIDA 2500, Komatsu 2000 and AIDA 15 machines in the Production Department 2 section. The results showed that there was still an excess workload experienced by operators where the highest physical workload was experienced by operators working on AIDA 15 machines by 118.11%. With the results showing that there is still an excess physical workload experienced by the operators, it is estimated that it is necessary to hold overtime hours for operators because the excess workload is not too large and is considered to be still manageable in the presence of overtime hours.